Broadcasters’ Leadership Traits and Audiences’ Loyalty With the Moderating Role of Self-Construal: An Exploratory Study - Huang, Yidan; Lee, Yi Hsuan; Chang, Gin; Ma, Jun; Wang, Guanyin (Frontiers in Psychology, 2021)
Although considerable attention has been paid to the application of leadership in virtual communities, the field of live broadcasting has not been involved. This paper aimed to explore how different broadcaster leadership traits (charismatic, authoritarian, servant) influence audiences’ loyalty (cognitive, conative). And audience self-construal was chosen as a key moderator. Hierarchical linear modelling was adopted for the analysis. This research found that broadcasters with servant and charismatic leadership traits positively affected cognitive loyalty. Broadcasters with service leadership traits also had a positive effect on conative loyalty. In addition, independent self-construal negatively (positively) moderated the relationship between servant (authoritarian) leadership and cognitive (conative) loyalty. Furthermore, interdependent self-construal negatively (positively) moderated the relationship between charismatic (authoritarian) leadership and conative loyalty. These conclusions extend the understanding of broadcasters’ traits and audiences’ psychology in relation to the booming phenomenon of live streaming and can help platform managers motivate audiences’ loyalty on these platforms.